Health Issues and Immunological Assessment Related to Wuhan's COVID-19 Survivors: A Multicenter Follow-Up Study - Mei, Qi; Wang, Fei; Yang, Yang; Hu, Guangyuan; Guo, Suihuai; Zhang, Qing; Bryant, Amy; Zhang, Lingjie; Kurts, Christian; Wei, Li; Yuan, Xianglin; Li, Jian (Frontiers in Medicine, 2021)
Background Currently, a large number of hospitalized COVID-19 patients have met clinical discharge criteria and have been discharged, little is known about sequelae and herd immunity, two important factor influencing the life quality and safety of COVID-19 survivors. Methods Discharged COVID-19 patients from 4 medical facilities in Wuhan, China were followed to record and investigate possible post-COVID-19 sequelae and herd immunity. After hospital discharge, patients reported to fangcang shelter hospitals for an initial 14-day period of mandatory clinical monitoring. After release from these shelter hospitals, patients returned home for self-quarantine. RT-qPCR was used for SARS-CoV-2 detection. Colloidal gold-based immunochromatographic strip assay (ICGSA) was used for anti-SARS-CoV-2 IgG and IgM antibody testing. Data for this study are derived from case reports, medical records and self-reports. Results A total of 3677 COVID-19 survivors (median age 59 years, IQR: 47-68, range 10-98; 55.5% female) who released from 4 hospitals in Wuhan, China, between Jan 18th and Mar. 29th, 2020, were followed for a median of 144 days (IQR: 135-157). During follow-up, 976 (26.5%) patients had at least 1 post-COVID-19 sequela. The incidence of post-COVID-19 sequelae among elderly COVID-19 survivors (age>=60) was slightly increased compared to that of young COVID-19 survivors (age<60; relative risk 1.05 [95% CI 1.02-1.10], p=0.007). During follow-up, a dramatic reduction of anti-SARS-CoV-2 IgG (88.0% [95% CI 84.2-90.4]) and IgM (93.2% [95% CI 88.5-96.4]) antibodies was observed. Among these COVID-19 survivors, 1.2% (n=45) retested-positive for SARS-CoV-2 and 1.0% (n=37) died during follow-up. Of those who died during follow-up, 70.3% were male and all were negative for both IgG and IgM, except one person was IgG-positive. Conclusions Our study documents significant post-COVID-19 sequelae that impair function of multiple organ systems in COVID-19 survivors, suggesting that the long-term effects of this disease will negatively impact survivors’ quality of life, continue to strain health care systems and result in extended periods of lost productivity. Further, female gender and anti-SARS-CoV-2 immunity may play an essential role in the survival after COVID-19 infection.